Technical Efficiency of Small-Scale Pig Farming in Indonesia - Ester Nurani Keraru; Harianto Harianto; Yusalina Yusalina (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2023)
Live pigs are still the mainstay of livestock sub-sector exports inIndonesia. Although pig farming in Indonesia has competitivenessin the international market, its productivity shows a decliningcondition. The purpose of this research is to measure the level oftechnical efficiency of small-scale pig breeding and fatteningbusinesses. The data used come from the results of the FarmHousehold Survey conducted by the Central Bureau of Statistics(BPS). The survey was conducted in 20 provinces in Indonesia,with a sample size of 6,681 small-scale or household-scale pigfarming. The research used the Stochastic Production Frontier(SPF) model to measure the level of technical efficiency of pigfarming and used the maximum likelihood method to estimate it. The results showed that the level of technical efficiency of pigfarming is relatively low. The average technical efficiency level offattening pig farming is higher than that of the breeding. Thefactors of farming experience, market orientation, and feed typecombination have a positive influence in improving efficiency. Public policies that improve pig farmers' access to farm inputs andmarkets are expected to significantly improve the productivity ofsmall-scale pig farming.